A Hybrid Particle‐Field Coarse‐Grained Molecular Model for Pluronics Water Mixtures1. Issue 17 (17th June 2013) - De Nicola, Antonio; Kawakatsu, Toshihiro; Milano, Giuseppe; Milano, Giuseppe; Venditto, Vincenzo; Oliva, Leone
Abstract In the framework of a hybrid particle‐field simulation technique where self‐consistent field (SCF) theory and molecular dynamics (MD) are combined, specific coarse‐grained (CG) models for Pluronic block copolymers are developed. In particular, the behavior of the model in the correct reproduction of micellar and non‐micellar phases has been tested for Pluronic L62 and L64. At different temperature and polymer contents of the water–polymer mixture, the proposed model is able to correctly describe the different morphologies that are experimentally found. The proposed CG models, still very close to atomistic ones, allow the reconstruction of full atomistic structures by applying suitable reverse mapping techniques. This opens the way to all atom description of these systems.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>